2011
DOI: 10.1007/s11434-011-4651-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of decadal-centennial-scale changes in East Asian summer monsoon circulation and precipitation during the Medieval Warm Period and Little Ice Age and in the present day

Abstract: Using meteorological observations, proxies of precipitation and temperature, and climate simulation outputs, we synthetically analyzed the regularities of decadal-centennial-scale changes in the summer thermal contrast between land and ocean and summer precipitation over the East Asian monsoon region during the past millennium; compared the basic characteristics of the East Asian summer monsoon (EASM) circulation and precipitation in the present day, the Little Ice Age (LIA) and the Medieval Warm Period (MWP);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…During the LIA, the opposite conditions existed. On the basis of a reconstruction of the Asian-Pacific Oscillation (APO), reflecting the thermal contrast between the Asian continent and northern Pacific, Zhou et al (2011) analyzed the variations of summer monsoon circulation and precipitation in eastern China. They suggested that the late MCA (early LIA) was the interval characterized by the strongest (weakest) Asian monsoon during the last millennium, and the spatial pattern of precipitation change was that of "Yellow River Catchment flood (drought) and Yangtze River Catchment drought (flood)".…”
Section: "Northesouth" Mode Of Hydroclimatic Variabilitymentioning
confidence: 99%
“…During the LIA, the opposite conditions existed. On the basis of a reconstruction of the Asian-Pacific Oscillation (APO), reflecting the thermal contrast between the Asian continent and northern Pacific, Zhou et al (2011) analyzed the variations of summer monsoon circulation and precipitation in eastern China. They suggested that the late MCA (early LIA) was the interval characterized by the strongest (weakest) Asian monsoon during the last millennium, and the spatial pattern of precipitation change was that of "Yellow River Catchment flood (drought) and Yangtze River Catchment drought (flood)".…”
Section: "Northesouth" Mode Of Hydroclimatic Variabilitymentioning
confidence: 99%
“…As a subtropical monsoon, the EASM is usually characterized by prevailing lower-tropospheric southerly winds. In addition, the monsoon precipitation over eastern China occurs in front of the maximum southerly wind centers, i.e., the rain belt known as the Meiyu Front in China, which lies on the northwestern flank of the North Pacific Subtropical High (Zhao et al, 2007b;Zhou et al, 2011;. Thus, the prevailing southerly winds/Subtropical…”
Section: Differences In Easm Rainfall Response Between Northern and Smentioning
confidence: 99%
“…The result exhibits more rainfall anomalies over northern China and less rainfall over the Yangtze River. This relationship between APO and summer precipitation over eastern China occurs not only during 1900–200920 and past 150 years71 but also throughout the past millennium2122232475. Summer rainfall anomalies associated with the paleo-APO during the Holocene also exhibit a similar pattern, which implies that this relationship between APO and summer rainfall over eastern China also occurs on a longer precessional scale.…”
Section: Summary and Discussionmentioning
confidence: 69%
“…A higher (lower) APO index often represents a stronger (weaker) thermal contrast between the Eurasian continent and the North Pacific Ocean. The APO index also sufficiently represents the long-term changes in the EASM rainfall over the past century20 and millennium21222324.…”
mentioning
confidence: 99%